ANALISA TINGKAT KEPUASAN REKANAN PADA CV KARYA ABSHOR PEMATANG SIANTAR MENGGUNAKAN ALGORITMA C4.5 - Ardilla, Ririn; Andani, Sundari Retno; Safii, M. (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
CV Karya Abshor Pematang Siantar is a company engaged in the procurement of goods and services, where this company can meet consumer needs such as operational support equipment, photocopy printing, contractors, leveransir, distributors and suppliers. There are many goods and services procurement businesses that offer various promos, prizes, and at low prices. If the customer is not satisfied with it, all will be in vain. The purpose of this study is to help CV owners. Karya Abshor knows the benchmark for partner satisfaction to be able to compete with other partner companies. Researchers will analyze partner satisfaction with attributes of service, performance, speed, convenience, cooperation, and satisfaction. By utilizing data mining techniques from the three tests that have been carried out on the partner satisfaction dataset distributed to 73 partners, it can be predicted using the C4.5 algorithm (decision tree) with an accuracy result of 95.45% with the help of the RapidMiner 8.1 tool. With these results, it can be used to measure the level of partner satisfaction with the procurement company CV Karya Abshor.[1] The author suggests that this research can be developed again using other methods and algorithms to get a comparison of results and steps to use them. And it's best to use more data and attributes to produce more accurate rules and be able to compare the classification process.